Analisis Laporan Keuangan Bank BCA Syariah Periode 2017-2021 Menggunakan Metode CAMEL - Anita Nurcahyani; Dailibas Dailibas (Jurnal Ilmiah Wahana Pendidikan, 2023)
The camel method is a method that is often used in assessing the soundness of a bank, in this method, there are five aspects assessed, namely (capital, asset quality, management, profits, and liquidity). These five factors are interrelated with each other in providing information related to the level of the soundness of a bank, if one of these aspects experiences problems it will affect other aspects. Thus the purpose of this study is to determine the level of soundness at PT Bank BCA Syariah using the CAMEL method in the 2017 to 2021 period, the ratios used include CAR, NPF, ROA, NPM and FDR. The data used in this research is secondary data, namely financial reports from 2017 to 2021.